2019
DOI: 10.1172/jci.insight.129240
|View full text |Cite
|
Sign up to set email alerts
|

Brain pharmacology of intrathecal antisense oligonucleotides revealed through multimodal imaging

Abstract: CMG were employees of Invicro, LLC when the studies were performed. JMS is currently an employee of Biogen Inc. NJA, LK, and ROC are employees of the University of Southampton. MB is an employee of 3D Imaging, and AV was an employee of Biogen Inc. at the time that this work was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 44 publications
5
72
0
Order By: Relevance
“…Studies with radiolabeled oligonucleotides and immunohistochemical studies with a phosphorothioate ASO–specific antibody have yielded insights into the ASO pharmacokinetics ( 8–10 ), but insights into ASO distribution in different cell types and subcellular compartments is typically lost. Fluorescence microscopy studies involving ASOs and siRNAs conjugated to fluorescent tags have made it possible to visualize ASOs ( 11–13 ), but those studies also have limitations. First, modifying NATs with fluorescent dyes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with radiolabeled oligonucleotides and immunohistochemical studies with a phosphorothioate ASO–specific antibody have yielded insights into the ASO pharmacokinetics ( 8–10 ), but insights into ASO distribution in different cell types and subcellular compartments is typically lost. Fluorescence microscopy studies involving ASOs and siRNAs conjugated to fluorescent tags have made it possible to visualize ASOs ( 11–13 ), but those studies also have limitations. First, modifying NATs with fluorescent dyes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Viral delivery of gene therapy achieves good CNS distribution but does not effectively target non-neuronal cells (46). Recently, we showed that following IT bolus injection in rats, ASO distributes rostrally in the CSF along the neuroaxis and rapidly adheres to pia and arterial walls, consistent with perivascular entry into the CNS (20). Over time, ASO accumulates in all major CNS cell types presumably by receptor mediated endocytosis (47).…”
Section: Csf Volume Scaling Across Species To Predict Aso Tissue Concmentioning
confidence: 97%
“…Antisense oligonucleotides (ASOs) are chemically modified single-stranded nucleic acids of [16][17][18][19][20][21][22][23][24][25] nucleotides in length that bind complementary RNA via Watson-Crick hybridization and can modulate the expression of genes by harnessing a variety of mechanisms (1). To reduce the expression of genes, ASOs can be designed to harness the RNase H1 mechanism (referred to herein as gapmers) (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain regional analysis was done using a 3-dimensional mouse brain atlas available as the VivoQuant software plug-in. The 3D brain atlas is based on the Paxinos-Franklin atlas registered to a series of high-resolution magnetic resonance imaging with 100 µm near isotropic data and has been applied in other studies [15][16][17] . The brain was segmented into 14 regions within the skull of each animal using the CT as the reference for automatic registration.…”
Section: Data Analyses Of [ 18 F]fdg Uptakementioning
confidence: 99%